CHALLENGES AND SOLUTIONS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE AT SCHOOLS - Shavkidinova, Dilnavoz (Журнал иностранных языков и лингвистики, 2023)
This study discusses the difficulties that teachers face when teaching English. Teaching English as a foreign language is a difficult task, especially in situations where English serves a very limited purpose. The challenges of teaching English as well as the perspectives of English language teachers in dealing with these challenges in the classroom is highlighted and investigated. A number of issues have arisen and solutions have been proposed.